Analisis Perilaku Konsumen dan Pembelian Impulsif Pada E-commerce Shopee - Nadia Nur Laillatul Rifqiah; Mas Ghoniyyul Hamid; Edita Rachma Kamila (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to analyze consumer behavior and impulse buying on the Shopee e-commerce platform, focusing on the young age group between 18 to 30 years old. In the digital era, e-commerce has changed the way of shopping, offering greater convenience and accessibility for consumers. The methodology used is a quantitative approach with the Technology Acceptance Model (TAM) model, which involves collecting data through questionnaires to 50-100 respondents. The results of the study indicate that consumer behavior has a significant influence on purchasing decisions, while impulse buying has no direct effect. These findings indicate that factors such as promotions and social trends play an important role in driving purchasing behavior among young consumers. This study provides insights for e-commerce managers in designing more effective marketing strategies to improve the online shopping experience.